Crab As A Coconut Oil Separating Agent - Sebastian Margino (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1991)
The role of sterilized and nonsterilized crab extract on the separation of coconut oil was examined using grated coconut meat as substrate. Sterilized crab extract was prepared by suspension and centrifugation of crushed crab and then filtrated using Millipore Utter. Sterilized crab extract has proteolytic activity but not lipolytic one. It was found that the sterilized crab extract supported the growth of proteolytic microbes, isolated from fermentation process of coconut oil. Both sterilized and nonsterilized crab extract gave no significant difference in the quantity of coconut oil obtained. However, coconut oil from the sterilized crab extract has better quality. The peroxide value of coconut oil from unsterilized crab extract was higher than that of standard quality of coconut oil according to SII and AOCS. The possible roles of crab inoculum in fermentation process of coconut oil are discussed.